A Socioemotional Wealth Approach to CEO Career Horizons in Family Firms - Strike, Vanessa M.; Berrone, Pascual; Sapp, Stephen G.; Congiu, Lorenzo (Journal of Management Studies, 2015)
ABSTRACTThis paper challenges the predominant view that as CEOs near retirement, they forgo risky long‐term strategic choices and instead focus on decisions that enhance their own short‐term self‐interests. Drawing on the socioemotional wealth (SEW) literature, we argue that unlike near‐retirement CEOs in widely held firms, near‐retirement CEOs in family firms are more concerned about transgenerational control and the legacy that they pass on to future generations. We further contend that the priority of SEW dimensions can change within family firms depending on the CEO's time to retirement. Consequently, near‐retirement CEOs in family firms differ from their counterparts in non‐family firms in that they are willing to continue to engage in international acquisitions as they approach retirement, despite the potential short‐term risks. We further hypothesize that this effect depends on whether the CEO is a family member, whether the CEO is succeeded by another family member, and whether the CEO is the founder. In analysing 3432 family and non‐family firm‐year observations from the S&P 500 for the period between 1997 and 2009, we find support for our hypotheses. Subsequent analyses indicate that near retirement, family CEOs acquire larger and culturally closer targets than their non‐family counterparts. Our paper confirms the need to more fully consider the characteristics of owners and managers in analyses of the CEO career horizon problem.